Consequences of a congested soccer calendar on team performance - Rey-Eiras, E.; Lago-Penas, C.; Casais-Martinez, L.; Lago-Ballesteros, J. (World Congress of Performance Analysis of Sport VIII, 2008)
There is a considerable variation in the number of matches played per season by clubs in the Spanish Soccer. In addition to the normal league matches, the top teams have to play some games of the UCL on midweek evenings. This study focuses on the question of whether a period with a busy match schedule can lead to fatigue and increase the risk of poor team performance. The results of the empirical analysis showed that playing a UCL match on midweek (UCL match) did not have a statistical significant effect on team performance. Consequently, UEFA Champions League teams did not have an important disadvantage in the domestic league compared with non-UEFA Champions League. These results are in disagreement with the findings of Ekstrand et al. (1983) and Ekstrand et al. (2004). Perhaps this is down to the sample and to the performance indicator selected in the studies. Secondly, the effect of a busy soccer schedule on the results of Champions League debutants is the opposite of that expected. The probability of winning vs losing is higher for Champions League debutants when they play a midweek match than when they play only one game a week. That is, Champions League debutants performed above their normal standard at the weekend when they played a Champions League midweek match. Many coaches maintain that an athlete´s level of preparation is also elevated by participation in competitions. Participation in competitions does assist the athletes to reach a high state of readiness for the next competition. During such competitions, the athletes have the opportunity to test all training factors in the most specific way. Perhaps, during a certain extent a top team can cope with a busy match schedule. Future studies should determine the ideal duration of the competitive phase in professional soccer. As far as the frequency and the number of matches are concerned, the time required for recovery between matches should be considered. A limitation of this study is that only weekend league matches and midweek Champions League games were considered in the analysis. Other midweek games should also be considered. There will be included UEFA Cup games, Spanish Cup games or even midweek international games which will involve most of the players of the top teams. The study also did not consider the midweek activity of the opponents of the Spanish Champions League teams.